Comparison of quadriceps muscle contractile properties during the recovery phase after treadmill and deep water running - Rankin, R. R.; Vicenzino, B. (1999)
This study compared the effects of deep water running (DWR) and treadmill running (TR) performed for 20 minutes at an intensity of 70% of estimated maximum heart rate. Eight healthy distance runners who were familiar with DWR had their quadriceps contractile properties examined before and 24 hours after control, DWR and TR sessions. Force response to electrical stimulation at low frequency (LFF,20Hz) and high frequency (HFF,50Hz) was used to monitor the recovery of muscle fatigue. The LFF recovery profile indicated that there was a significant difference between TR and control and between DWR and TR (p<0.025), but not between a no-exercise control session and DWR. The HFF recovery profile differed to the LFF in that there was no significant difference between control and TR. In TR there was a significant difference between LFF and HFF, which was not present for the control or DWR conditions. These differing recovery profiles suggest that DWR does not produce the same extent of muscle fatigue as TR and may provide a different muscle recruitment pattern that has potential benefits as an exercise recovery modality.